Pengaruh Kesadaran Wajib Pajak, Sistem Samsat Drive Thru, Dan Program Pemutihan Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Di Samsat Kota Denpasar - I Gede Indra Suardinata; Ni Komang Sumadi; Ni Putu Trisna Windika Pratiwi (Hita Akuntansi dan Keuangan, 2026)
Compliance is motivation to comply with existing rules. In the taxation, tax compliance is about fulfilling the obligation to pay taxes voluntarily to support national development. This study aims to investigate how Taxpayer Awareness, the Samsat Drive Thru System, and the Tax Amnesty Program affect motor vehicle taxpayer compliance at the Denpasar City Samsat. The study involved taxpayers registered at the Denpasar City Samsat with a total population of 1,019,523 people. From this population, 100 taxpayers were selected using a simple random sampling method with the Slovin formula. The results of the study indicate that the three factors—taxpayer awareness, the Samsat Drive Thru system, and the tax amnesty program—all have a positive and significant influence on motor vehicle taxpayer compliance.